Kemacetan di Jalan Raya dalam Karya Lukis Kontemporer - Adhe Irawan Suja, Drs. Idran Wakidi, Drs. Erfahmi, M.Sn. (Serupa The Journal of Art Education, 2016)
Congestion is one of the events that occurred on the highway that can cause long queues of motor vehicles, so that the traffic flow becomes choked. Problems arising from congestion is the time the riders wasted unnecessarily. The purpose of disclosure is to provide knowledge congestion problems in complying with the awareness of the importance of traffic rambu2, skilled in driving to avoid themselves from the congestion to the creation of road conditions are arranged neatly away from the congestion. Ten paintings contemporary style created : 1), “Pindah Jalur” 2), “Pengemis Jalanan I” 3), Pengemis Jalanan II” 4), “Melawan Arus” 5), “Kurang Konsentrasi I” 6), “Kurang Konsentrasi II” 7), “Para Pekerja” 8), “Pengemis dan Sapu” 9), “Angkutan Kota” 10), “Dilarang Berhenti”. The results of this work have an understanding of the importance of obeying traffic laws that can be used as a moral message to the wider community.